Utilization of the “Horse Whip” Plant Into Processed Health Drinks for PKK Mothers in Bondoyudo Village Lumajang District - Frimha Purnamawati; Nani Sintiawati; Niswatul Imsiyah; Irliana Faiqotul Himmah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Bondoyudo Village, Sukodono District, Lumajang Regency is one of the villages with a variety of potential crops ranging from bananas, tomatoes, vegetables and other fruit crops, not separated from that Bondoyudo Village also has many "horse whip" plants which are basically wild plants that grow in fields, roadsides and hills, where there has also been research that the "horse whip" plant can be used to maintain a healthy body, almost all parts of the plant, can be used as medicine. Roots, flowers, stems or leaves. The horse whip plant can treat urinary tract infections, sore throat due to inflammation (pharyngitis), cough, rheumatism, and irregular menstruation. Especially for its flowers and stems, it can be used for the treatment of hepatitis A or inflammation of the liver. While the roots, can be used for the treatment of vaginal discharge (leukorrhea). However, the knowledge to process it is still unfamiliar to the community, especially the Bondoyudo Village PKK mothers who consider that this plant is only a wild plant that is only thrown away. So with the potential possessed by the village, there are many advantages in empowering the community, especially women by utilizing the "horse whip" plant. Based on these issues, women's empowerment is an important part of the process of improving the quality of Human Resources (HR) through training activities. The method that will be used in this Community Empowerment is by transferring technology, namely transferring knowledge as well as providing training on how to make health drinks made from horse whip plants to the Women's Farmers Group of Bondoyudo Village, Sukodono District, Lumajang Regency.